2008
DOI: 10.1021/la702310t
|View full text |Cite
|
Sign up to set email alerts
|

Protein-Resistant Poly(ethylene oxide)-Grafted Surfaces:  Chain Density-Dependent Multiple Mechanisms of Action

Abstract: A clear understanding of the mechanisms responsible for the protein-resistant nature of end-tethered poly(ethylene oxide) (PEO) surfaces remains elusive. A barrier to improved understanding is the fact that many of the factors involved (chain length, chain density, hydration, conformation, and distal chemistry) are inherently correlated. We hypothesize that, by comparing systems of variable but precisely known chain density, it should be possible to gain additional insight into the effects of the other factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
180
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(198 citation statements)
references
References 45 publications
13
180
5
Order By: Relevance
“…This dynamic range is comparable to many existing synthetic polymer brush systems and suggests that these materials may serve as an attractive complement or alternative to synthetic systems in specific settings 24,39 . It is also conceivable that this dynamic range could be shifted, widened, or narrowed in interesting ways by exerting more control over the grafting density, such as by using cloud point grafting to achieve very dense brushes 40,41 . Furthermore, we have demonstrated that we can use proteases to reduce the height of the brush in situ by cleaving the constituent chains at well-defined points.…”
Section: Discussionmentioning
confidence: 99%
“…This dynamic range is comparable to many existing synthetic polymer brush systems and suggests that these materials may serve as an attractive complement or alternative to synthetic systems in specific settings 24,39 . It is also conceivable that this dynamic range could be shifted, widened, or narrowed in interesting ways by exerting more control over the grafting density, such as by using cloud point grafting to achieve very dense brushes 40,41 . Furthermore, we have demonstrated that we can use proteases to reduce the height of the brush in situ by cleaving the constituent chains at well-defined points.…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming clear that chain density and, thus, conformation are critical factors in the successful lowprotein-fouling properties of PEG and PEG-like films [19,[35][36][37]. In a study by Fick et al [17], PEG self-assembled monolayers were reported to be highly protein resistant when they contain a solvated densely grafted brush of only 40 Å thick, which correlates to a chain length of only 11 ethylene glycol units.…”
Section: % Compositionmentioning
confidence: 99%
“…4 The ability for a given PEG functionalized surface to resist fouling is thought to be mainly dependent on the graft density and molecular weight (M W ) of PEG used, both of which are key properties that decide the conformation of PEG chains on surfaces. [5][6][7] For example. in the case of high or low graft density, PEG chains are arranged in either the "brush" or "mushroom" conformation, respectively.…”
Section: Introductionmentioning
confidence: 99%